المعوقات والالتزامات الأسریة التي تواجھ المراة في عملھا (Journal of the College of Education for Women, 2019)
This research aims to understand the main problems and familycommitments faced by working women, and make proposals that would stop orlessen them, the researcher made questionnaire , applied on a sample of (20)university female teachers, the study showed that the main problems in respect totheir importance as: Anxiety of leaving children at home alone, the weak role of thenurseries and kindergartens in taking care of the children, relative large number ofchildren per family which would lead to more commitments, and the unavailabilityof convenient working arrangement for working mothers.